Relationship between usage of smartphone dating application with sexual risk behaviours among young adult in Kuching and Samarahan Division - Jesica Jenah, Ramping (Universiti Malaysia Sarawak (UNIMAS), 2020)
Smartphone dating applications have become tremendously popular in Malaysia and globally. This study aims to see the prevalence of smartphone dating application usage and sexual risk behaviours as well as to examine the relationship between the use of smartphone dating application and sexual risk behaviour among young adult in Kuching and Samarahan Division. Data collection was done through ILOVEKUCHING Facebook page. Subjects completed self-administered structured questionnaire regarding the current use of smartphone dating application, their sexual behaviours and sociodemographic. Chi-Square test was done in order to see the associative factors between both sociodemographic, usage of smartphone dating application with sexual risk behaviours. Two hundred and eighty respondents included in current study data analysis with the mean age of the respondents was 20.8(SD=1.638). The prevalence of using smartphone dating application is 25% (n=70) and the prevalence of sexually active is 27.1 % (n=76). The prevalence of unprotected sexual activities among respondents is 85.5% (n=66), early age of sexual initiation is 11.8% (n=9) , multiple sexual partners in their lifetimes is 59.2% (n=45), sexual activities under alcohol influence is 50% (n=38) and sexual activities under recreational drug influence is 11.8% (n=9). Chi-square test found that usage smartphone dating application significantly associated with unprotected sexual activities X2 (1,n=76) =13.494, p=0.000 and having multiple partners within past 3 months X2 (1, n=76) =5.380, p=0.020. For Sociodemographic variables, being a Christian associated with early sexual initiation (below 16 years old) X2 (1, n=76) =7.054, p=0.029 as well as sexual activities under drug influence, X2 (1, n=76) =9.770, p=0.008. The present study found a strong association between sexual risk behaviour and usage of smartphone dating application in which user of smartphone dating application has higher risk in committing risky sexual behaviour as compared to non-user among young adult population. Primary and secondary intervention can be focused on these high risk group in the future.